A comprehensive study of the radiative properties of NO—a first step toward a complete air opacity. (21st September 2022) - Zammit, Mark C; Leiding, Jeffery A; Colgan, James; Even, Wesley; Fontes, Christopher J; Timmermans, Eddy
Abstract: In this paper we propose a methodology to calculate the radiative properties of the diatomic molecular constituents of air, and utilize the present approach to model the radiative properties of nitrogen monoxide, NO. We also investigate the important physics involved in calculating accurate radiative quantities for air, such as the Planck and Rosseland mean opacities, and emission and absorption coefficients, as well as the couplings accounted for in rovibrational calculations. Complete active space self-consistent field multi-reference configuration interaction (CAS-MRCI) calculations were performed in order to model the NO X 2 Π, a 4 Π, b 4 Σ −, 1 2 Σ +, 2 2 Σ +, 3 2 Σ +, G 2 Σ −, B ′ 2 Δ, ( C, B ) 2 2 Π, ( H ′, L ) 3 2 Π, and 1 2 Φ adiabatic states, and calculate the respective molecular data. The γ X 2 Π − A 2 Σ +, ɛ X 2 Π − D 2 Σ +, β ′ X 2 Π − B ′ 2 Δ, '11 000 Å' A 2 Σ + − D 2 Σ +, 'infrared' X 2 Π − X 2 Π and X 2 Π − ( C, B ) 2 2 Π ( δ and β ) band systems are investigated in monochromatic spectra calculations, as well as the Ogawa a 4 Π − b 4 Σ − band and several other band systems. Several conclusions are drawn, such as the importance of including the Ogawa band, which has not been included in previous air radiative models or comprehensive line-list calculations, as well as the importance of performing coupled rovibrational line-list calculations in order to accurately calculate the Rosseland means. We also found that the additional band systems modeled here contribute significantly to the total Planck and Rosseland means.